Application Of Pressure Biofeedback Unit As Part Of Ergonomics Assessment Tools For Assessing Back Pain Among Computer Users - Padmanathan, Vinothini; Halim, Isa; Too, Yi Wei (World Academy Of Research In Science And Engineering (WARSE), 2019)
The decrease in the back muscle strength, especially Transverse Abdominus (TrA) muscle can be an early symptom for the occurrence of back pain among individual. The Pressure Biofeedback Unit (PBU) was frequently used in the clinical setting to assess the TrA strength level among back pain patients. However, in the ergonomics setting, lack of studies available to look into the usefulness of the PBU to assess the back muscle strength level, especially the TrA among the working population who are having back pain symptoms. Therefore the current pilot study was conducted among ten computer users to look into the validity of the PBU in assessing the TrA strength level in identifying the early symptom of back pain. The validity of PBU results was compared with the Standardized Nordic Questionnaire results in identifying the back pain symptom among computer users. The chi-square analysis revealed that there was no any significant differences between PBU results and Standardized Nordic Questionnaire results in screening the early symptom of back pain. In conclusion, the current study revealed that the PBU can be an useful tool in the ergonomics assessment to identify the early symptom of back pain among computer users.